The market strategies of Esporte Interativo: regionalization and the foreign capital in Brazilian television - Gomes dos Santos, Anderson David (2016)
In this article, we are particularly interested in two movements of the Esporte Interativo in Brazilian pay TV: regionalization, from the transmission of the “Nordestão”; and the relationship with global groups, with particular reference to its acquisition by Turner. Both movements occurred in the same period, working for the Esporte Interativo become a major sports channel, even not being one of the operators Sky and Net due to the Globo Group entry barriers. The perspective of this study is that of Political Economy of Communication and Culture (PEC), but we use also authors from Industrial Economy like Kupfer (2002). This mix is common in Brazilian PEC (Bolaño, 1988 & 2004; Brittos, 2005; Santos, 2013).